An examination of entrance criteria for international medical graduates (IMGs) into Canadian psychiatry residency programs - Soma, Ashok; Myatt, Matthew; McKenna, Mario; Ganesan, Soma; Leung, Ka Wai (Canadian Medical Education Journal, 2017)
Background: Although international medical graduates (IMGs) are essential in health care service delivery, a gap exists in the literature about how IMGs are selected into psychiatry residency programs in Canada. The purpose of this study was to identify the relative weight or importance that Canadian program directors (PDs) of psychiatry place on certain selection criteria when matching IMGs into residency programs. Methods: We electronically distributed a web-based questionnaire to 16 university residency program directors of psychiatry in Canada. Program Directors were asked to rate the importance of 43 selection criteria using 5-point Likert Scales. Criteria were grouped into six domains: academic criteria, extracurricular activities, supporting information, behavioural issues of concern, medical school country, and other education. Mean total values for each set of criteria were calculated and used to create rank orders within each domain. Results: Eight out of 16 program directors responded. Our analysis indicated that academics and behavioral issues of concern were the most important selection criteria. Conclusion: Our findings provide valuable insight about the perspectives of Program Directors toward IMGs who apply for psychiatry residency programs in Canada. Further studies are needed to better understand which criteria contribute to IMGs’ performances as psychiatric residents.